Clostridium difficile Molecular Epidemiology in a Prospective Cohort of Canadian Children Compared with Cases of C. difficile Infection. (4th October 2017) - Lloyd, Colin; Parsons, Brendon; Du, Tim; Golding, George R; Lee, Bonita; Chui, Linda; Freedman, Stephen; ,
Abstract: Background: Clostridium difficile is a notorious nosocomial pathogen, but little is known regarding the colonization commonly observed in children. It is suspected that C. difficile carriage in infants is a reservoir for toxigenic strains. To test this hypothesis, we sought to determine the genetic relatedness between a prospective cohort of C. difficile toxin gene positive healthy children and those with acute gastroenteritis (AGE) and strains identified in adult and pediatric C. difficile infection (CDI) cases from Alberta, Canada. Additionally, we compared C. difficile toxin production in healthy and AGE children. Methods: C. difficile was cultured from 97 hospitalized CDI cases ( n = 79 adult; n = 18 pediatric) from stool samples tested positive for toxigenic C. difficile by C.DIFF QUIK CHEK COMPLETE® enzyme immunoassay (EIA) in 2015 and samples tested positive for toxin genes by the Luminex xTAG® Gastrointestinal Pathogen Panel from a prospective cohort of 59 children with AGE seeking care at the emergency department and 17 healthy children attending public health clinics. Isolates were then characterized by PCR-ribotyping, pulsed-field gel electrophoresis (PFGE), PCR of the tcdA, tcdB, tcdC, and cdtB genes and C. difficile toxigenicity by EIA for a subset of 14 healthy and 45 AGE children. Results: Ribotype 106 was predominant among all pediatric isolates ( n = 21, 27.6% AGE and healthy children; n = 5, 27.8% pediatric CDI) and ribotype 027 in adult CDIs ( n = 35, 44.3%). Eighteen ribotypes were shared between children and CDI cases ( n = 134, 77.5%). Sixteen unique ribotype and PFGE patterns ( n = 84, 48.6%) were identified in two or more cohorts. Similar toxin gene profiles were observed across the three cohorts, but adult CDI isolates had a higher proportion of binary toxin positive isolates ( n = 42, 53.2%) compared with children ( n = 3, 3.95%) and pediatric CDI ( n = 0). C. difficile toxigenicity was similar ( P = 0.23) amongst the subset of healthy ( n = 6, 42.9%) and AGE ( n = 28, 62.2%) children. Conclusion: Production of C. difficile toxins in children was not significantly associated with symptoms of AGE. C. difficile strains found in children were similar to those from CDI cases; especially pediatric cases. This suggests that strains might be shared, but the development of CDI may be related to factors other than C. difficile strain type. Disclosures: All authors: No reported disclosures.